Pharmacological Manipulation of Wnt/β-Catenin Signaling Pathway in Human Neural Precursor Cells Alters Their Differentiation Potential and Neuronal Yield - Telias, Michael; Ben-Yosef, Dalit (Frontiers in Molecular Neuroscience, 2021)
The canonical Wnt/β-catenin pathway is a master-regulator of cell fate during embryonic and adult neurogenesis and is therefore a major pharmacological target in basic and clinical research. Chemical manipulation of Wnt signaling during in-vitro neuronal differentiation of stem cells can alter both the quantity and the quality of the derived neurons. Accordingly, the use of Wnt activators and blockers has become an integral part of differentiation protocols applied to stem cells in recent years. Here, we investigated the effects of the glycogen synthase kinase-3β inhibitor CHIR99021, which upregulates β-catenin agonizing Wnt; and the tankyrase-1/2 inhibitor XAV939, which downregulates β-catenin antagonizing Wnt. Both drugs and their potential neurogenic and anti-neurogenic effects were studied using stable lines human neural precursor cells (hNPCs), derived from embryonic stem cells, which can be induced to generate mature neurons by chemically-defined conditions. We found that Wnt-agonism by CHIR99021 promotes induction of neural differentiation, while also reducing cell proliferation and survival. This effect was not synergistic with those of pro-neural growth factors during long-term neuronal differentiation. Conversely, antagonism of Wnt by XAV939 consistently prevented neuronal progression of hNPCs. We show here how these two drugs can be used to manipulate cell fate and how self-renewing hNPCs can be used as reliable human in-vitro drug-screening platforms.